Efecto de altos niveles de nitrogeno en parron de vid cv. sultanina - Retamales A, J.=700 1 Razeto M, B.
(ES, En)
Ilus., 7 ref.
Keywords: VID; ABONOS NITROGENADOS; PRODUCCION; CHILE; PARRA; EXCESO DE NITROGENO; AGRICULTURA TECNICA